Pelatihan Pembuatan Sabun Cuci Piring Sebagai Upaya Peningkatan Keterampilan Anak Panti Asuhan Putera Muhammadiyah Kota Medan - Suherman Suherman; Surya Sevi Wijayanna Lumban Tobing; Muharnif Muharnif; Adinda Juwita Nasution; Ilmi Ilmi (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
Training in making dish soap is a community service activity that aims to improve children's skills. This activity was carried out at the Muhammadiyah Putra Orphanage, Medan City, with the target of adolescent foster children. The methods used include counseling, direct practice in making dish soap, and discussion and evaluation of the results of the activities. The training materials include introductions to raw materials, the mixing process, and packaging techniques. The results of the activity showed that participants were able to understand and independently practice the process of making dish soap. In addition, participants gained basic knowledge of business opportunities in the household product industry. This activity has a positive impact on life skills and on fostering entrepreneurial motivation among foster children. Training in making dish soap is expected to be a sustainable skill provision and has the potential to be developed as an independent business in the orphanage environment.